Investigation on nickel ferrite nanowire device exhibiting negative differential resistance — a first-principles investigation - Nagarajan, V.; Chandiramouli, R (Condensed Matter Physics, 2017)
The electronic property of NiFe₂O₄ nanowire device is investigated through nonequilibrium Green’s functions
(NEGF) in combination with density functional theory (DFT). The electronic transport properties of NiFe₂O₄
nanowire are studied in terms of density of states, transmission spectrum and I–V characteristics. The density
of states gets modified with the applied bias voltage across NiFe₂O₄ nanowire device, the density of charge is
observed both in the valence band and in the conduction band on increasing the bias voltage. The transmission spectrum of NiFe₂O₄ nanowire device gives the insights on the transition of electrons at different energy
intervals. The findings of the present work suggest that NiFe₂O₄ nanowire device can be used as negative differential resistance (NDR) device and its NDR property can be tuned with the bias voltage, which may be used
in microwave device, memory devices and in fast switching devices. Електроннi властивостi NiFe₂O₄ нанодротового пристрою дослiджується з використанням методу нерiвноважних функцiй Грiна в комбiнацiї з теорiєю функцiоналу густини. Властивостi електронного переносу
NiFe₂O₄ нанодроту вивчаються в термiнах густини станiв, спектру трансмiсiї та I–V характеристик. Густина станiв змiнюється при прикладаннi змiщувальної напруги через NiFe₂O₄ нанодротовий пристрiй,
густина заряду спостерiгається як у валентнiй зонi, так i в зонi провiдностi при збiльшеннi напруги змiщення. Спектр трансмiсiї NiFe₂O₄ нанодротового пристрою дає уявлення про перехiд електронiв на рiзних
енергетичних iнтервалах. Результати даної роботи наводять на думку, що NiFe₂O₄ нанодротовий пристрiй може бути використаний як негативний диференцiйний опiр, i ця його властивiсть може бути регульована за допомогою напруги змiщення, що може мати потенцiйне використання у мiкрохвильових
пристроях, пристроях пам’ятi i в перемикальних пристроях.